A triplex real-time PCR method to detect African swine fever virus gene-deleted and wild type strains - Yang, Hao; Peng, Zhong; Song, Wenbo; Zhang, Chen; Fan, Jie; Chen, Hongjian; Hua, Lin; Pei, Jie; Tang, Xibiao; Chen, Huanchun; Wu, Bin (Frontiers in Veterinary Science, 2022)
Currently there is still no effective vaccines and drugs available for African swine fever virus (ASFV), a life-threatening virus to domestic pigs and wild boars. Therefore, accurate diagnosis is important for the prevention and control of the virus. In this study, we developed a triplex real-time PCR method to detect and differentiate ASFV gene-deleted and wild type strains based on three viral genes B646L, MGF_360-14L gene, and CD2v. Standard curves plotted showed that there was a strong linear correlation (R2＞0.99) between Ct values and the corresponding copy numbers of synthesized standard plasmids. The detection limits of the method for B646L, MGF_360-14L, and CD2v were 78.9 copies/μl, 47.0 copies/μl, and 82.1 copies/μl, respectively. Detection results of different types of swine viruses showed that the method only gave amplification curves to ASFV. Finally, we found the triplex real-time PCR method developed in this study displayed better results on detecting the laboratory sample mocks, and it could be used as a supplemental method to detect ASFV genotype I strains. These findings suggest that the triplex real-time PCR method developed in this study have good specificity and sensitivity. This triplex real-time PCR method might also represent an effective tool for the detection of ASFV gene-deleted and wild type strains.